Seroprevalence of five neglected parasitic diseases among immigrants accessing five infectious and tropical diseases units in Italy: a cross-sectional study. (May 2017) - Martelli, G.; Di Girolamo, C.; Zammarchi, L.; Angheben, A.; Morandi, M.; Tais, S.; Degani, M.; El Hamad, I.; Caligaris, S.; Ciannameo, A.; Grilli, E.; Urbinati, L.; et al.
Abstract: Objective: This multicentre cross-sectional study aims to estimate the prevalence of five neglected tropical diseases (Chagas disease, filariasis, schistosomiasis, strongyloidiasis and toxocariasis) among immigrants accessing health care facilities in five Italian cities (Bologna, Brescia, Florence, Rome, Verona). Methods: Individuals underwent a different set of serological tests, according to country of origin and presence of eosinophilia. Seropositive patients were treated and further followed up. Results: A total of 930 adult immigrants were enrolled: 477 men (51.3%), 445 women (47.9%), eight transgender (0.8%); median age was 37.81 years (range 18–80 years). Most of them had come from the African continent (405/930, 43.5%), the rest from East Europe, South America and Asia, and 9.6% (89/930) were diagnosed with at least one of the infections under study. Seroprevalence of each specific infection varied from 3.9% (7/180) for Chagas disease to 9.7% (11/113) for toxocariasis. Seropositive people were more likely to be 35–40 years old and male, and to come from South East Asia, sub-Saharan Africa or South America. Conclusions: The results of our study confirm that neglected tropical diseases represent a substantial health problem among immigrants and highlight the need to address this emerging public health issue.